A multilevel investigation of motivational cultural intelligence, organizational diversity climate, and cultural sales: Evidence from U.S. real estate firms. - Chen, Xiao-Ping; Liu, Dong; Portnoy, Rebecca (Journal of Applied Psychology, 2012)
Adopting a multilevel theoretical framework, the authors examined how motivational cultural intelligence influences individual cultural sales–the number of housing transactions occurring between people of different cultural origins. Data from 305 real estate agents employed at 26 real estate firms in the United States demonstrated that an individual's motivational cultural intelligence is positively related to his or her cultural sales. This positive relationship is enhanced by the firm's motivational cultural intelligence and diversity climate. The authors discuss the theoretical and practical implications of their findings in a workplace context that involves cross-cultural interpersonal interactions.